Size, value, and momentum in Polish equity returns: Local or international factors? - Adam Zaremba; Przemysław Konieczka (International Journal of Management and Economics, 2017)
This paper tests the performance of the Capital Asset Pricing Model (CAPM) and the Fama-French three-factor and Carhart four-factor models on the Polish market. We use stock level data from April 2001 to January 2014 and find strong evidence for value and momentum effects, but only weak evidence for size premium. We formed portfolios double-sorted on size and book-to-market ratios, as well as on size and momentum, and we explain their returns with the above-mentioned asset pricing models. The CAPM is rejected and the three-factor and four-factor models perform well for the size and B/M sorted portfolios, but fail to explain returns on the size and momentum sorted portfolios. With the exception of the momentum factor, local Polish factors are not correlated with their European and global counterparts, suggesting market segmentation. Finally, the international value, size and momentum factors perform poorly in explaining cross-sectional variation in stock returns on the Polish market.
Keywords: G11; G12; G14; G15; 650; value effect; size effect; momentum effect; Fama-French three-factor model; Carhart four-factor model; Polish market; asset pricing; market segmentation